PISA trends, social changes, and education reforms. Issue 5 (18th August 2017) - Aloisi, Cesare; Tymms, Peter
ABSTRACT: The stability of educational test results from the Programme for International Student Assessment (PISA) over 15 years was examined, and the influence of demographics and social capital was assessed, as was the impact of educational reforms. The test results were remarkably stable, with correlations up to 0.99 for country-level results over 2 cycles. Despite this stability, trends were observed with scores generally rising year on year, but so too were the socioeconomic indicators. Together with measures of gender, immigration, Organisation for Economic Co-operation and Development (OECD) membership and first language, these variables went a long way to account for the rising scores. Case studies suggest that the clearest impact of reforms on test scores amount to an annual effect size of around 0.02. The paper argues for the greater prominence of fairer adjusted PISA league tables and suggests that multidisciplinary approaches to educational data analyses and policy advice are needed.